Print and Power in Early Modern Europe (1500-1800) - Lamal, Nina; Cumby, Jamie; Helmers, Helmer J. (Library of the Written Word - The Handpress World, 2021)
Print, in the early modern period, could make or break power. This volume addresses one of the most urgent and topical questions in early modern history: how did European authorities use a new medium with such tremendous potential? The eighteen contributors develop new perspectives on the relationship between the rise of print and the changing relationships between subjects and rulers by analysing print's role in early modern bureaucracy, the techniques of printed propaganda, genres, and strategies of state communication. While print is often still thought of as an emancipating and destabilizing force of change in early modern societies, the resulting picture shows how instrumental print was in strengthening existing power structures. Readership: This volume will appeal to historians of early modern print culture as well as historians of media and anyone with broad interest in early modern cultural and political history.